Distribution of tetrodotoxin among tissues of pufferfish from Sabah and Sarawak waters - Mohd Nor Azman, A.; Samsur, M.; Othman, M. (Universiti Kebangsaan Malaysia, 2014)
Puffer fish, mainly from Tetraodontidae family known to possess a neurotoxin or tetrodotoxin (TTX) which can cause a puffer fish poisoning and adverse effect to human health. In current study, the tetrodotoxin (TTX) concentration in different tissues (liver, skin, muscle) of 14 species of puffer fish from Sabah and Sarawak waters were analysed and determined by application of liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS). Overall, extracted toxin for all specimens were shown to be toxic with result more than 0.2 μg/g as calculated based on TTX standard curve. Among the tissues, liver were found to be highest in TTX concentration (91.0 μg/g), followed by muscle (51.1 μg/g) and skin (6.87 μg/g). Moreover, TTX concentrations among puffer fish species were significantly differences (p<0.05) with Arothron immaculatus (275 μg/g) showed highest mean value, while the lowest value was detected in Lagocephalus lunaris (4.92 μg/g). From this finding, LC-MS/MS application could be a potential tools to determine the TTX and advisedly used as a procedure in screening of seafood for monitoring program. Furthermore, baseline data of TTX levels in selected puffer fish from the study could be important information and used as guideline in order to mitigate puffer fish poisoning cases especially in East Malaysia waters.